2016
DOI: 10.1590/1413-785220162404156575
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inside-Out and All-Inside Technique in Bucket-Handle Meniscus Tears

Abstract: Objective: To determine the outcomes after combined inside-out and all-inside repair technique of bucket-handle meniscus tears. Methods: A retrospective review was made of patients with bucket-handle meniscus tears repaired with combined techniques, using the all-inside technique in posterior meniscal tears and the inside-out technique in the middle part of the meniscal tears. Meniscal healing was assessed clinically using Barrett's criteria and MRI. Results: The study comprised 52 patients with a mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…For comparison, other publications have reported even greater success in outcomes: Yilmaz et al . 31 noted complete meniscal healing in all but one of 52 patients (mean age = 28.4 years) who underwent a combined inside-out and all-inside technique for repair of bucket-handle meniscus tears at a mean 31.3-month follow-up. Ahn et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For comparison, other publications have reported even greater success in outcomes: Yilmaz et al . 31 noted complete meniscal healing in all but one of 52 patients (mean age = 28.4 years) who underwent a combined inside-out and all-inside technique for repair of bucket-handle meniscus tears at a mean 31.3-month follow-up. Ahn et al .…”
Section: Discussionmentioning
confidence: 91%
“…For comparison, other publications have reported even greater success in outcomes: Yilmaz et al 31 noted complete meniscal healing in all but one of 52 patients (mean age = 28.4 years) who underwent a combined inside-out and allinside technique for repair of bucket-handle meniscus tears at a mean 31.3-month follow-up. Ahn et al 32 retrospectively evaluated 13 patients with a median age of 20 years at a median 4.0 years follow-up after modified all-inside or combination all-inside/outside-in repair of lateral meniscus bucket-handle tears.…”
Section: Discussionmentioning
confidence: 93%
“…We used a combined inside-out and all-inside modality with multiple suturing techniques to ensure stable and adequate fixation. This approach was approved as being appropriate by many researchers 1,2,[12][13][14][15] ; however, some authors have recorded better outcomes with all-inside repairs when compared with inside-out repairs. 12 Our assertion was similar to those of Yilmaz et al, 13 who found out that combined CHRONIC ISOLATED BUCKET-HANDLE MENISCAL TEAR e5 inside-out and all-inside meniscal repair technique is a successful and cost-effective treatment method in bucket-handle meniscus tears.…”
Section: Discussionmentioning
confidence: 99%
“…24 Among the most popular devices that assist the surgeon in meniscal repairs from the inside-out, we can mention the malleable needles attached to the suture thread, which have the disadvantage of needing 1 device for each suture, making the repair very costly. 25 There are malleable needles with a lumen that allow the use of a single kit in >1 point; however, these cannulas are fragile and sometimes crush and obstruct their lumen during use, requiring often 2 devices to repair extensive injuries. 2,26 We herein describe the meniscal suture technique using the Meniscus 4-All device, which is resistant and allows countless stitches with a single device (Table 1).…”
Section: Discussionmentioning
confidence: 99%